In vivo dynamics of Drosophila nuclear envelope components. - Katsani, K.R.; Karess, R.E.; Dostatni, N.; Doye, V. (Molecular Biology of the Cell, 2008)
Nuclear pore complexes (NPCs) are multisubunit protein entities embedded into the nuclear envelope (NE). Here, we examine the in vivo dynamics of the essential Drosophila nucleoporin Nup107 and several other NE-associated proteins during NE and NPCs disassembly and reassembly that take place within each mitosis. During both the rapid mitosis of syncytial embryos and the more conventional mitosis of larval neuroblasts, Nup107 is gradually released from the NE, but it remains partially confined to the nuclear (spindle) region up to late prometaphase, in contrast to nucleoporins detected by wheat germ agglutinin and lamins. We provide evidence that in all Drosophila cells, a structure derived from the NE persists throughout metaphase and early anaphase. Finally, we examined the dynamics of the spindle checkpoint proteins Mad2 and Mad1. During mitotic exit, Mad2 and Mad1 are actively imported back from the cytoplasm into the nucleus after the NE and NPCs have reformed, but they reassociate with the NE only later in G1, concomitantly with the recruitment of the basket nucleoporin Mtor (the Drosophila orthologue of vertebrate Tpr). Surprisingly, Drosophila Nup107 shows no evidence of localization to kinetochores, despite the demonstrated importance of this association in mammalian cells.